Interplay Between ACE2 and Angiotensin-(1-7) in the Regulation of Blood Pressure - Ferrario, Carlos M.; Jessup, Jewell A. (Current Hypertension Reviews, 2007)
The primacy of angiotensin II (Ang II) as the critical component mediating the multiple biological actions of the renin angiotensin system is undergoing a critical revision given the growth of the biochemical and physiological evidence demonstrating the existence of other proteins that, within the system, lead to the formation of alternate forms of angiotensin peptides. The persistent notion that Ang II is at the center of the mechanisms of action by which the renin angiotensin system exerts complex and pleiotropic effects on cellular growth, metabolism, and contraction has been challenged by the emerging understanding of the biochemical pathways entailing expression and function of the vasodilator/antigrowth properties of angiotensin-(1-7) [Ang-(1-7)], the role of the mas receptor as its ligand, and the cloning of a homologue of angiotensin converting enzyme (ACE2), which may limit the actions of Ang II by converting the peptide into Ang-(1-7). We analyze in this article the biochemical processing pathways leading to the formation of Ang-(1-7) from both angiotensin I and Ang II within the context of a functional paradigm that suggests that a deficit in the functional activity of the arm of the renin angiotensin system [ACE2/Ang-(1-7)/mas receptor] may play a critical role in the pathogenesis of hypertension.
Keywords: Angiotensin II